Complete mitogenome of the invasive bivalve Rangia cuneata - Gastineau, Romain (Mitochondrial DNA B Resour, 2019)
We sequenced the complete mitogenome of a Baltic Sea specimen of the invasive bivalve Rangia cuneata. The mitogenome is 18,993 bp long and encodes 13 proteins, 2 rRNAs, and 22 tRNAs. A large intergenic region between ND6 and ND2 contains an open reading frame that may originate from duplication of ND2. The R. cuneata mitogenome is rearranged in gene order relative to previously sequenced mitogenomes of Mactroidea.